2016
DOI: 10.1186/s12711-016-0263-4
|View full text |Cite
|
Sign up to set email alerts
|

From cow to cheese: genetic parameters of the flavour fingerprint of cheese investigated by direct-injection mass spectrometry (PTR-ToF-MS)

Abstract: BackgroundVolatile organic compounds determine important quality traits in cheese. The aim of this work was to infer genetic parameters of the profile of volatile compounds in cheese as revealed by direct-injection mass spectrometry of the headspace gas from model cheeses that were produced from milk samples from individual cows.MethodsA total of 1075 model cheeses were produced using raw whole-milk samples that were collected from individual Brown Swiss cows. Single spectrometry peaks and a combination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…These instruments combine the advantages of very rapid complete spectra acquisition and high mass resolving power that permits, for the low molecular weight VOCs, the determination of exact formula allowing for example analysis of isobaric compounds in food-flavour applications. 90 95 Other studies investigated the cow genetic parameters in relation with cheese flavour 96 Another study conducted on 20 samples of "Trentingrana" cheese concluded on the possibility to estimate sensory attributes (12 flavour attributes rated by a panel of eight assessors in a quantitative descriptive analysis QDA) by the PTR-MS spectral fingerprints through the use of partial least squares (PLS) data analyses. 104 However, the authors stressed that the presence of correlation between both sets of data does not indicate the presence of direct causality.…”
Section: Proton Transfer Reaction Msmentioning
confidence: 99%
See 1 more Smart Citation
“…These instruments combine the advantages of very rapid complete spectra acquisition and high mass resolving power that permits, for the low molecular weight VOCs, the determination of exact formula allowing for example analysis of isobaric compounds in food-flavour applications. 90 95 Other studies investigated the cow genetic parameters in relation with cheese flavour 96 Another study conducted on 20 samples of "Trentingrana" cheese concluded on the possibility to estimate sensory attributes (12 flavour attributes rated by a panel of eight assessors in a quantitative descriptive analysis QDA) by the PTR-MS spectral fingerprints through the use of partial least squares (PLS) data analyses. 104 However, the authors stressed that the presence of correlation between both sets of data does not indicate the presence of direct causality.…”
Section: Proton Transfer Reaction Msmentioning
confidence: 99%
“…An apple germplasm collection was comprehensively characterized as was the genetic control of apple volatilome and its interplay with fruit texture, while PTR‐ToF‐MS data enabled the mapping of quantitative trait loci related to apple volatilome . Other studies investigated the cow genetic parameters in relation with cheese flavour and the influence of dairy system and individual cow characteristics on the volatile fingerprint of cheeses . Other selected recent examples concern the distinction of species of chili peppers, the geographical origin of truffle and the impact of seasonal variations, the distinction between Mediterranean landraces and modern varieties of durum wheat or the ripening of mangoes .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we used PTR-ToF-MS to study the effect of dairy system, individual sources of variation (e.g. lactation stage and parity), and genetics on the volatile fingerprint of model cheeses (Bergamaschi, Aprea et al 2015;Bergamaschi et al 2016). Results showed that dairy system of origin of the milk processed was an important source of variation on about 23% of the spectrometric peaks characterising the volatile profile of ripened cheeses.…”
Section: Introductionmentioning
confidence: 99%
“…Direct injection mass spectrometry based on soft ionization could be considered as a potential candidate for the future development of EGA systems. Instead of hard ionization techniques, mass detectors based on soft ionization result in mass spectra that are easier to interpret . Among soft ionization mass detectors, proton transfer reaction mass spectrometry (PTR‐MS) has become a benchmark method for the simultaneous real‐time monitoring of VOCs .…”
Section: Introductionmentioning
confidence: 99%
“…Instead of hard ionization techniques, mass detectors based on soft ionization result in mass spectra that are easier to interpret. 9 Among soft ionization mass detectors, 10 proton transfer reaction mass spectrometry (PTR-MS) has become a benchmark method for the simultaneous real-time monitoring of VOCs. 11 The working principle behind PTR-MS is based on the protonation of volatile molecules (VOCs) with hydronium ions (H 3 O + ).…”
Section: Introductionmentioning
confidence: 99%